Does Monopoly Power Lead to Higher Prices? - A Microeconomic Analysis in the Context of Bangladesh - Akter, Masuda; Akter, Mahmuda; Ali, Md. Mokshud (International Journal of Business and Economics, 2026)
This study investigates the correlation between monopoly power and pricing behavior in Bangladesh, emphasizing whether concentrated market arrangements result in elevated consumer prices. The research utilizes microeconomic theory and qualitative documentary analysis to examine market concentration, entry barriers, and regulatory frameworks in critical sectors of Bangladesh. The research uses a blend of pricing indices, sector-specific market share statistics, and competition enforcement records to evaluate the impact of market power on price dynamics. The findings indicate that a higher concentration is frequently linked to increased pricing, although this correlation is not guaranteed. Regulatory actions, budgetary policies, and the legitimacy of enforcement significantly mediate the impacts of monopolistic power. The research indicates that price escalations in concentrated sectors are affected by both market power and external disturbances, including exchange rate variations and macroeconomic factors. The study additionally suggests a comprehensive econometric approach for next investigations, emphasizing sector-specific data and the influence of market behavior on price results. This study enhances the comprehension of monopolistic power dynamics in emerging economies such as Bangladesh, providing policy recommendations to enhance market transparency, competition policy, and enforcement mechanisms.